2016
DOI: 10.1136/jech-2015-205680
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a school-based intervention programme regarding adherence to a healthy diet in children and adolescents from disadvantaged areas in Greece: the DIATROFI study

Abstract: As low SES groups tend to adopt unhealthier dietary choices, it is of the outmost importance to take action for the promotion of healthy eating, directed especially to these at risk populations. School-based nutritional programmes can be considered as an effective policy measure towards this direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 41 publications
3
39
0
3
Order By: Relevance
“…Be that as it may, the dietary patterns of children and adolescents in Greece over the last decades are shifting away from the traditional Greek diet, towards an unhealthier direction (12)(13)(14)(15)(16) . At the same time, approximately 40% of children and adolescents are either overweight or obese, exhibiting one of the highest prevalence rates of pediatric overweight and obesity in Europe (16)(17)(18) .…”
Section: Introductionmentioning
confidence: 99%
“…Be that as it may, the dietary patterns of children and adolescents in Greece over the last decades are shifting away from the traditional Greek diet, towards an unhealthier direction (12)(13)(14)(15)(16) . At the same time, approximately 40% of children and adolescents are either overweight or obese, exhibiting one of the highest prevalence rates of pediatric overweight and obesity in Europe (16)(17)(18) .…”
Section: Introductionmentioning
confidence: 99%
“…Most primary school children spend approximately 6 hours per day at school [19] with most of this time (65%) being sedentary [20] . School-based interventions have been shown to be effective in reducing health inequalities [21] , [22] , promoting healthy behaviours generally [23] , increasing physical activity [12] and may also be helpful in preventing excessive sedentary behaviour in children [24] . However, there appears to be variability in how each of these studies measured sedentary time as an outcome, therefore leading to uncertainties in objective reliability in intervention efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Parents reported that their child’s intake of fresh produce increased after participating, with most reporting that the nutrition education component was effective. Similarly, nutrition education has been integrated into a free-school meal intervention in low SES schools in parts of Greece [41]. Here, provision of a free meal, education about a healthy diet and physical activity, as well as cooking demonstrations for parents, resulted in significant increases in consumption of multiple healthful foods, and some movement towards a Mediterranean diet pattern, which is suggested to have health benefits.…”
Section: Resultsmentioning
confidence: 99%